Pengaruh Model Pembelajaran Think Pair Share (TPS) Terhadap Hasil Belajar Ekonomi Pada Siswa Kelas X Di SMA Kutabumi I Tangerang Banten - Khoirudin Khoirudin; Supriyanah Supriyanah (Jurnal Inovasi dan Kreativitas (JIKa), 2021)
Abstract Problem: From observations and preliminary research conducted, information is obtained that the daily test for the field of Economics study is still below the KKM, in this case SMA Kutabumi I Tangerang, West Java set the KKM for the field of Economics study is 70. However, the average student learning outcomes X for the first daily test reaches a value of 60.22 so 40% of students must take remedial. Purpose: To determine the effect of the Think Pair Share Model on Economics Learning Outcomes in Class X Students at SMA Kotabumi Tangerang, Banten. Methodology: Methodology This research uses quantitative methods which are carried out through the experimental method, namely by giving different treatments to the control class and the experimental class, then from the treatment, the learning outcomes that may be achieved by the two groups will be compared. Results/Findings: learning through Think Pair Share model has an average learning outcome of 85.26, while the lowest score is 73.00 and the highest score is 97.00. This value is higher than the achievement of student learning outcomes who are given learning through Problem Based Instruction (PBI) where the average value of learning outcomes is 63.68 and the lowest score is 57.00 and the highest score is 73.00. Paper type : Eksperiment. Keywords: Think Pair Share Model, Economic Learning Outcomes,